THE CHALLENGES TO LEARN MALAY LANGUAGE AMONG FOREIGN UNIVERSITY STUDENTS THROUGH ONLINE LEARNING - Mohamad Maswan, Norfaizadatul Akma; Abdul Samat, Siti Rohani; Mohd Nasir, Nurul Farhanah (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The Malay Language is Malaysia's national language and learning it is very essential. Since the Covid-19 epidemic, most educational institutions have used online learning as one of their teaching strategies. Unfortunately, studying and reading a language through online instruction can be challenging, and some students may find this way to be very tedious. This research investigates the difficulties that foreign students and lecturers may encounter when learning and teaching Malay language online. To address the research issues, a qualitative method was employed in this study, which drew information from secondary sources such books, chosen articles, and official reports. The initial results indicate that there are numerous foreign students and numerous difficulties for both foreign students and instructors, as they are unable to acquire the language as effectively as they could in completely physical classes. In addition, students struggle to concentrate and face other challenges such as poor internet access, sluggish online videos, and difficulty understanding instructors' pronunciation of the Malay language.